2019
DOI: 10.1074/jbc.tm118.004162
|View full text |Cite
|
Sign up to set email alerts
|

Milestones in transcription and chromatin published in the Journal of Biological Chemistry

Abstract: During Herbert Tabor's tenure as Editor-in-Chief from 1971 to 2010, JBC has published many seminal papers in the fields of chromatin structure, epigenetics, and regulation of transcription in eukaryotes. As of this writing, more than 21,000 studies on gene transcription at the molecular level have been published in JBC since 1971. This brief review will attempt to highlight some of these ground-breaking discoveries and show how early studies published in JBC have influenced current research. Papers published i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 126 publications
0
3
0
Order By: Relevance
“…However, its rigidity and Zn 2+ binding hydroxamate permitted AR-42 to be modeled into the HDAC1 active site with a high degree of confidence (Figure a). AR-42 was predicted to bind to Zn 2+ with its hydroxamate group chelating in a bidentate manner similar to other ligands bound to Class I HDACs. , The model suggested that the adjacent aromatic ring of AR-42 occupied the narrow 11 Å hydrophobic cavity, making pi -interactions with both Phe150 and Phe205. The amide NH made a hydrogen bond with the side chain carboxylate of Asp99 and the terminal phenyl ring filled a hydrophobic pocket lined by residues Phe150, Pro29, Leu271, and His28.…”
Section: Resultsmentioning
confidence: 96%
“…However, its rigidity and Zn 2+ binding hydroxamate permitted AR-42 to be modeled into the HDAC1 active site with a high degree of confidence (Figure a). AR-42 was predicted to bind to Zn 2+ with its hydroxamate group chelating in a bidentate manner similar to other ligands bound to Class I HDACs. , The model suggested that the adjacent aromatic ring of AR-42 occupied the narrow 11 Å hydrophobic cavity, making pi -interactions with both Phe150 and Phe205. The amide NH made a hydrogen bond with the side chain carboxylate of Asp99 and the terminal phenyl ring filled a hydrophobic pocket lined by residues Phe150, Pro29, Leu271, and His28.…”
Section: Resultsmentioning
confidence: 96%
“…Epigenetic approaches, to "make the abnormal gene behave like a normal gene," are being tested in Friedreich's ataxia with small molecules, ASOs, and artificial transcription factors that enable transcription to "read-through" the GAA expansion "and make protein anyway [49]." Micro RNAs have been looked at in spinocerebellar ataxia as an epigenetic way to modify mutant DNA transcription [50][51][52][53].…”
Section: Genetic and Epigenetic Approachesmentioning
confidence: 99%
“…Similarly, Judy Bond discusses the explosion of work appearing in JBC during Herb Tabor's editorship in the field of proteases and how prophetic the JBC leadership was in recognizing this burgeoning area of biological chemistry (3). Joel Gottesfeld has attempted the heroic task of showing the upsurge of work during this time in the field of transcription and the transcriptional machinery, with linkages to key papers in JBC published under Herb Tabor's leadership (4). The list continues: Heidi Hamm describes the impact of JBC and Herb Tabor on G-protein signaling (5).…”
mentioning
confidence: 99%